PENGARUH KONTRIBUSI PAJAK DAERAH TERHADAP TINGKAT KEMANDIRIAN DAERAH (Survei di Kota Lhokseumawe) - Dewi Susianti; Murhabban Murhabban; Zulkarnaini Zulkarnaini (LPPM STIE Lhokseumawe, 2017)
This study is to analyze the effect of the local taxes contribute to the level of local independence in Lhokseumawe. The data used in this research is secondary data time series period 2006-2015. The source data comes from DPKAD Office of Lhokseumawe. The data processing is done with the help of a simple linear equation model. The results showed that: The local taxes contribution significantly influence the level of local independence in Lhokseumawe. This is because the local tax is one component of the PAD’s most dominant as the reception area. Local tax contributions have a strong relationship with the level of local independence in Lhokseumawe because local taxes can sustain the level of the region’s autonomy. Local tax contributions have the ability to explain the impact on the level of independence in Lhokseumawe is 56.3%. While the remaining 43.7% is influenced by other variables outside the research models such as levies, local revenues, general allocation fund, a special allocation of funds, and others.